Pancreatectomy with arterial resection is superior to palliation in patients with borderline resectable or locally advanced pancreatic cancer. Issue 2 (February 2019) - Del Chiaro, Marco; Rangelova, Elena; Halimi, Asif; Ateeb, Zeeshan; Scandavini, Chiara; Valente, Roberto; Segersvärd, Ralf; Arnelo, Urban; Verbeke, Caroline S.
Abstract: Background: Few studies have investigated the outcome of pancreatectomy associated with artery resection (PAR). Methods: Retrospective analysis of a cohort of operated borderline or locally advanced pancreatic cancer patients with surgically confirmed arterial involvement. Short and long-term outcome were analyzed and compared in patients who underwent PAR (Group 1) and palliative surgery (Group 2). Results: Of 73 patients who underwent surgical exploration with intent of resection, 34 underwent PAR (±venous resection) (Group 1) and 39 underwent palliation (Group 2). 23 patients (67.7%) in Group 1 underwent combined artery-vein resection (AVR). Operation time was longer and blood loss higher in group 1 compared to group 2. There were no differences in post-operative mortality (2.9% vs 2.6%, p = 0.9) and post-operative surgical complications (38.2% vs 25.6%, p = 0.2). The 1, 3 and 5 years survival in Group 1 was superior to Group 2 (63.7%, 23.4% and Q3 23.4% vs 41.7%, 3.2% and 0, p = 0.003). Conclusion: PAR seems to be safe and feasible in well selected patients and associated with an advantage of survival compared to palliation, in patients affected by locally advanced pancreatic cancer.